Proceedings of the Eighteenth ACM SIGSOFT International Symposium on Foundations of Software Engineering 2010
DOI: 10.1145/1882291.1882331
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced test case selection approach for model-based testing

Abstract: In recent years, Model-Based Testing (MBT) has attracted an increasingly wide interest from industry and academia. MBT allows automatic generation of a large and comprehensive set of test cases from system models (e.g., state machines), which leads to the systematic testing of the system. However, even when using simple test strategies, applying MBT in large industrial systems often leads to generating large sets of test cases that cannot possibly be executed within time and cost constraints. In this situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 28 publications
(43 reference statements)
0
29
0
2
Order By: Relevance
“…Hemmati, et al [7] propose an alternative technique to MBT, which is supposed to overcome one of MBT's most important issues, that is, the enormous number of generated test cases which impact negatively on both time and cost.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemmati, et al [7] propose an alternative technique to MBT, which is supposed to overcome one of MBT's most important issues, that is, the enormous number of generated test cases which impact negatively on both time and cost.…”
Section: Related Workmentioning
confidence: 99%
“…Their approach implements a smart test case selection technique based on genetic algorithms which choose a test suite from the large pool of generated test cases to be executed based on resources and maximum fault coverage criteria, thus extending traditional MBT into a more time/cost saving version [7].…”
Section: Related Workmentioning
confidence: 99%
“…Though in SMBT a test path represents an encoded abstract test case, the test path can be described at different levels of details. In [2], we studied three encodings for a test path in UML state machine: state-based, transition-based, and triggerguard-based, and reported that trigger-guard-based encoding is the most effective one in terms of fault detection, where a test path(tp) is represented as:…”
Section: Similarity-based Test Case Selectionmentioning
confidence: 99%
“…In [2,3], we proposed a similarity-based selection technique for testing based on UML state machines (SMBT). We compared different similarity measures in terms of what information from the test cases they have to evaluate (test case encodings) and how this evaluation should be done (similarity functions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation